Study the Effect of Ferula hermonis Extract on HepG2 cell line culture (Journal of the College of Basic Education, 2022)
Ferula hermonis Boiss (Apiaceae) is known in the Midleast as "zallouh". In the last decade, scientists paid attention to study chemistry and biological activity of the plant. In this study Ferula hermonis were collected and evaluated for cytotoxic activity. The plant was extracted with methanol The cytotoxic effect of the extracts was examined in-vitro on human cell line (Human liver carcinoma cell line HepG2). Results were shown that significant decrease of HepG2 cells viability. The effect of F. hermonis on cell viability of HepG2 cell line culture show that plant extract cause significant decrease ( p< 0.05) of HepG2 cell viability, and this decrease in cell viability is increased with the increasing the extract concentrations in comparison with the negative control, and the growth inhibition percentage reach to (78.3%).